The regulation of online political micro-targeting in Europe - Tom Dobber; Ronan Ó Fathaigh; Frederik J. Zuiderveen Borgesius (Internet Policy Review, 2019)
In this paper, we examine how online political micro-targeting is regulated in Europe. While there are no specific rules on such micro-targeting, there are general rules that apply. We focus on three fields of law: data protection law, freedom of expression, and sector-specific rules for political advertising; for the latter we examine four countries. We argue that the rules in the General Data Protection Regulation (GDPR) are necessary, but not sufficient. We show that political advertising, including online political micro-targeting, is protected by the right to freedom of expression. That right is not absolute, however. From a European human rights perspective, it is possible for lawmakers to limit the possibilities for political advertising. Indeed, some countries ban TV advertising for political parties during elections.
Keywords: 300; Online political micro-targeting; Data protection; Privacy; Freedom of expression; Advertising law; Elections